PERAN PEMERINTAH DESA DALAM MENINGKATKAN PARTISIPASI MASYARAKAT UNTUK MEMBAYAR PAJAK BUMI DAN BANGUNAN (STUDI DI KECAMATAN PRINGGASELA): The Role of the Village Government in Increasing Community Participation in Paying Land and Building Tax (A Study in Pringgasela District) - Saleh, M.; Sarkawi, Sarkawi; Khair, H. A. (Ganec Swara, 2026)
This study aims to evaluate the contribution of village governments in stimulating citizen involvement regarding Land and Building Tax (PBB) payments. Employing empirical research methods through juridical, conceptual, and sociological approaches, the data were analyzed based on field observations and authentic legal interpretations. The research findings indicate that village government strategies for enhancing tax compliance are highly dependent on the social dynamics and unique characteristics of each region. Given that these factors significantly influence public awareness, more integrated measures and cross-sector collaboration are necessary to optimize citizen participation in fulfilling their tax obligations.